Influência de aspectos pessoais no efeito país-de-origem: impactos da geração e do self estendido do consumidor na intenção de compra - Moraes, Sergio Garrido (2018)
The effect of a product or brand country of origin on a consumer's purchase intention has been one of the most relevant topics in international marketing research. Interest in this topic of research is growing as the reduction of trade barriers, the development of global markets, the internationalization of production and advances in logistics increase the availability of foreign goods across borders, increasing competition between products, brands, and countries. However, several limitations are pointed out in this type of study: lack of market segmentation, research design that does not reproduce conditions close to reality, lack of useful recommendations for managers, lack of theoretical foundation. The present thesis developed and tested a theoretical model that demonstrated that the country of origin effect does not act directly, but mediated by personal factors of the consumer, such as dispositions (ethnocentrism) and involvement with the product category. Developed and validated, too, a scale that measures the consumer's self-connection to a country, just as the self also connects to brands, as has already been demonstrated in the literature. In line with recent research, it has demonstrated that personal factors impact on how the consumer rates a country's image in its consumption decisions. It also demonstrated that country, brand, and product interact differently when studying different segments of consumers. To reach the objectives, several studies were done to validate the Self-Country Connection scale, following the best practices indicated in the literature. A model has also been developed that relates personal aspects of the consumer with the intention of buying a global brand. The model was teste using PLS-SEM. As a result, it is concluded that consumers of different generations feel differently about the country, the brand and the category of product when forming their intention to buy. It is recommended that the design of the country of origin research consider the personal aspects of the consumer, such as self, involvement, dispositions for consumption of foreign products and brands, and, above all, market segmentation, differentiating consumers who react differently to the country of origin.